Sistem Informasi Pendaftaran Dan Pendataan Berbasis Online di MA Ibrahimy Secang Banyuwangi - Baijuri, Achmad; Haza Mahendra, Yusril (Universitas Muhammadiyah Riau, 2024)
Abstract The registration stage is a very important first step in the process of entering the MA Ibrahimy Secang School. Currently, the MA Ibrahimy Secang School is still using the manual registration process as usual. Prospective students who wish to register must come directly to the school to collect the registration form and return it after filling it out. In addition, if a report is needed, the admin must check one by one the student data registered in the agenda book and make a report based on that information. To overcome this obstacle, it is necessary to develop an online registration system at the MA Ibrahimy Secang School. This system allows prospective students to register directly and get announcements without having to come to the school to pick up the form. The development of this system uses the waterfall method and involves the use of use case diagrams, class diagrams, and activity diagrams in system modeling. The result of this research is an online registration and data collection application.